The Effect of 2024 Presidential Election Announcement on Stock Abnormal Return in Energy and Consumer Non-Cyclical Sectors - Janssen Evan Sugiono; Cliff Kohardinata (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Major political events often serve as important catalysts for financial markets while simultaneously attracting public attention. A presidential announcement does not only mark leadership transition, but also conveys a strong signal that investors may interpret as a basis for formulating investment strategies, in line with signaling theory. The Indonesia elected president places energy and food downstreaming as key policy priorities; therefore, the energy sector and the consumer non-cyclical sector receive particular attention and are expected to be directly affected by the policy direction. This condition has the potential to shape market expectations and generate differing investor reactions across the two sectors. The aim of this study to examine the effect of the 2024 Presidential announcement and sectoral differences (energy sector and consumer non-cyclical sector) on stock abnormal returns in the energy and consumer non-cyclical sectors listed on the Indonesia Stock Exchange. The method applied is a multiple linear regression approach using data from 155 listed firms over the observation period of 13–27 March 2024. The results show that the presidential announcement has a significant negative effect on abnormal returns, indicating that abnormal returns (market reactions) are lower after the 2024 presidential announcement. This finding suggests that the market had anticipated the political direction prior to the official announcement. In addition, sectoral variable has a significant effect on abnormal returns, indicating that abnormal returns in the consumer non-cyclical sector are higher than those in the energy sector. This finding reflects investor optimism that food downstreaming will be realized more quickly than energy downstreaming, which requires a lengthier process.